Ensuring that biomedical AI benefits diverse populations - James Zou (EBioMedicine, 2021)
Artificial Intelligence (AI) can potentially impact many aspects of human health, from basic research discovery to individual health assessment. It is critical that these advances in technology broadly benefit diverse populations from around the world. This can be challenging because AI algorithms are often developed on non-representative samples and evaluated based on narrow metrics. Here we outline key challenges to biomedical AI in outcome design, data collection and technology evaluation, and use examples from precision health to illustrate how bias and health disparity may arise in each stage. We then suggest both short term approaches—more diverse data collection and AI monitoring—and longer term structural changes in funding, publications, and education to address these challenges.